ANALISIS KOMBINASI ALGORITMA FUZZY INFERENCE SYSTEM (FIS) DAN FUZZY K-NEAREST NEIGHBOR (FKNN) PADA SISTEM KLASIFIKASI PENYAKIT GIGI - Prandana, Randy; Suwilo, Saib; Mawengkang, Herman (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
The combination of the FIS and FKNN methods in the dental disease classification system gives good results. FIS is used to classify training data and FKNN serves to provide the best results by eliminating ambiguity in data classification.